A negative T‐wave in electrocardiogram at 50 years predicted lifetime mortality in a random population‐based cohort. Issue 11 (10th September 2020) - Sjöland, Helen; Fu, Michael; Caidahl, Kenneth; Hansson, Per‐Olof
Abstract: Background: Severe electrocardiographic (ECG) abnormalities in asymptomatic subjects correlate with cardiovascular risk. Hypothesis: The role of minor ECG abnormalities is less well‐known. We evaluated the association between a negative T‐wave and mortality, as a possible marker for prognosis. Methods: A prospective, population‐based cohort, examined at 50 years, and followed until death. Time to death (event rates) and predictive role of a negative T‐wave (Cox regression) were analyzed. Results: Participants (n = 839) with a negative T‐wave (7.3%) had significantly higher blood pressure (BP) (mean systolic 157.9 mmHg vs 136.8 mmHg without negative T‐wave, P = <.0001). A negative T‐wave correlated with elevated risk (hazard ratio [HR] [95% CI] [confidence interval]) for all‐cause and cardiovascular (CV) death (1.59 (1.20‐2.11) P = .0012 vs 1.91 (1.34‐2.73) P = .0004). The association remained after excluding coexisting Q/QS patterns and ST‐junction/segment depression ECG abnormalities (1.66 [1.13‐2.44] P = .0098 for all‐cause vs 1.87 [1.13‐3.09] P = .015 for CV death). Death from other causes was not associated with a negative T‐wave. A major negative T‐wave carried higher risk than a minor (2.17 [1.25‐3.76] P = .0062 vs 1.78 [1.13‐2.79] P = .012) for CV death. Conclusion: A negative T‐wave at 50 years, in asymptomatic individuals, carried an increased risk of all‐cause and CV death during lifetime follow‐up.